Portal vein embolisation in a patient with situs inversus - Faria, Igor (BMJ Case Rep, 2018)
Portal vein embolisation (PVE) is a well-established technique used for patients who require major hepatic resections without sufficient volume of future remnant liver (FRL). We describe a case of PVE in a patient with situs inversus. Computed Tomography (CT) 4 weeks after the procedure demonstrated significant hypertrophy of the FRL. However, the surgical procedure was aborted due to signs of extrahepatic progression.